Occupational Asthma Due to Subtilisin: The Power of Specific Inhalation Challenge - Liviero, Filippo; Fabris, Laura; Biasioli, Marco; Favretto, Francesco; Mason, Paola (La Medicina del Lavoro, 2025)
We report the first confirmed case in Italy of occupational asthma caused by subtilisin in a healthcare worker involved in cleaning surgical instruments. The diagnosis was confirmed through a specific inhalation challenge (SIC) performed one year after the last exposure and after stopping inhaled corticosteroid therapy. An immediate reaction was observed after three minutes of exposure to diluted Neogiozym ™, with a 30% decrease in FEV1. This case highlights the diagnostic importance of SIC even for high-molecular-weight (HMW) agents and emphasizes the need to reconsider occupational asthma as a complex, evolving disease influenced by both host and environmental factors. The patient exhibited a Type-2-high phenotype despite negative skin prick tests and normal IgE levels, reinforcing the value of dynamic, multi-marker assessment in occupational endotyping. This case supports the broader use of SIC in occupational settings where allergen-specific IgE testing is limited.